Exploring English Teachers’ Challenges in Applying Motivational Strategies at Senior High School - Abdal, Rezkya; Sahril; Fitriyani; Muh.Tahir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the challenges faced by English teachers in implementing motivational strategies during English teaching at senior high school level. The research was conducted at SMAN 3 Luwu Timur using a descriptive qualitative method. Two English teachers teaching grade X were selected as participants through purposive sampling. Data were collected using classroom observation and interviews. The findings show that teacher encountered various challenges, including the diversity of students’ backgrounds, large class size, persistent use of native language, and lack of infrastructure. These challenges significantly hindered the effectiveness of motivational strategies in the learning process. Addressing the obstacle is crucial for improving students’ motivation in English Learning